Seasonal coastal residency and large-scale migration of two grey mullet species in temperate European waters - Jena E. Edwards; Anthonie D. Buijse; Hendrik V. Winter; Allert I. Bijleveld (Movement Ecology)
Abstract Grey mullets (family Mugilidae) are widespread across coastal, brackish, and freshwater habitats, and have supported fisheries for millennia. Despite their global distribution and commercial value, little is known about their movement ecology and its role in the co-existence of sympatric mullet species. Gaps in knowledge about migratory behaviour, seasonal occurrence, and movement scales have also impeded effective management, highlighting the need for further research. This study aimed to identify key habitats and timing of grey mullet presence across the Dutch Wadden Sea, North Sea, and freshwater areas, and to explore potential behavioral differences between two grey mullet species: thicklip mullet (Chelon labrosus) and thinlip mullet (Chelon ramada). Using acoustic telemetry, we tracked 86 tagged grey mullet over three years (thicklip mullet, N = 74; thinlip mullet, N = 12), combining data from 100 local acoustic receivers and the European Tracking Network. Both species were detected in the Wadden Sea from April to November, however, thinlip mullet arrived in the Wadden Sea earlier than thicklip mullet (median date = May 16 vs. June 7). Individual residency in the Wadden Sea lasted a median 97 days for thicklip mullet and 94 days for thinlip mullet. Thinlip mullet were also detected by more receivers and over a larger area than thicklip mullet, indicating differences in movement behaviour. Both species showed an affinity for receivers near major harbours, with thinlip mullet more often detected near fresh water outflows. Seasonal migrations between coastal and offshore waters were also observed, with one thinlip mullet returning to freshwater across consecutive years. North Sea detections spanned ten months, with a gap during the presumed spawning period (Jan–Feb). Our data suggest that thinlip mullet show a preference for deeper gullies while thicklip mullet may spend more time in shallow areas and flooded tidal flats. These findings highlight the importance of the Wadden Sea as a seasonal foraging ground and provide insights into the migratory patterns of grey mullets.